Physical Self-Concept on Unhealthy Eating Behavior in Young Adult Women - Sari, Dewi Kusuma Tanjung; Hermita, Martissya (Psychopreneur Journal, 2023)
Unhealthy eating behavior in young adults, especially women, needs to be considered to avoid the occurrence of diseases that lead to mortality, one of which influences harmful eating behavior is the physical self-concept in young adult women. This study aims to examine whether there is an effect of physical self-concept on unhealthy eating behavior in young adult women. Respondents in this study were 150 women with an age range of 19-30 years, who made dietary adjustments such as reducing meal frequency, reducing/not consuming certain types of food, regulating the composition of food consumed, consuming drugs/supplements to regulate body metabolism to lose/gain weight, or do strenuous exercise. This study used the unhealthy eating behavior scale from Van Strein et al (1986) and the physical self-concept scale from Hsu and Lu (2013). This study uses the linear regression method to examine the effect of physical self-concept on unhealthy eating behavior. The results of this study indicate that there is an influence between physical self-concept and unhealthy eating behavior in young adult women with the results of R square = 0,145 and contributed an influence of 14,5%. This means showing that the physical self-concept will affect unhealthy eating behavior.